THE EFFECT OF GREEN MARKETING AND BRAND IMAGE TOWARD PURCHASE DECISION ON THE FACE SHOP BANDUNG - Wahyu Liana; Farah Oktafani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This research was conducted to determine and analyze the effect of Green Marketing, Brand Image toward Purchasing Decisions. This research employs quantitative methods. Data collection techniques in this study used a questionnaire. Sampling was conducted using non-probability sampling with incidental sampling. The number of respondents are100 people. The data analysis technique used is descriptive analysis and multiple linear regression analysis. Based on the results of testing the hypothesis simultaneously that Green Marketing and Brand Image have a significant effect on purchasing decisions. Based on the results of partial hypothesis testing (t test) that partially Green Marketing has a significant effect on Purchasing Decisions and partially Brand Image has a significant effect on Purchasing Decisions. The conclusion of this research is that The Face Shop’s Green Marketing and Brand Image are already very good. Hence, it is hoped that The Face Shop can continue to maintain the quality of its products and make new innovations. Keywords: Green Marketing, Brand Image and Purchasing Decisions.